Lasiopodomys fuscus as an important intermediate host for Echinococcus multilocularis: isolation and phylogenetic identification of the parasite - Qi-Gang Cai; Xiu-Min Han; Yong-Hai Yang; Xue-Yong Zhang; Li-Qing Ma; Panagiotis Karanis; Yong-Hao Hu (BMC, 2018)
Abstract Background Echinococcus multilocularis causes alveolar echinococcosis (AE) and is widely prevalent in Qinghai Province, China, where a number of different species have been identified as hosts. However, limited information is available on the Qinghai vole (Lasiopodomys fuscus), which is hyper endemic to Qinghai Province and may represent a potential intermediate host of E. multilocularis. Thus, L. fuscus could contribute to the endemicity of AE in the area. Methods Fifty Qinghai voles were captured from Jigzhi County in Qinghai Province for the clinical identification of E. multilocularis infection via anatomical examination. Hydatid fluid was collected from vesicles of the livers in suspected voles and subjected to a microscopic examination and PCR assay based on the barcoding gene of cox 1. PCR-amplified segments were sequenced for a phylogenetic analysis. E. multilocularis-infected Qinghai voles were morphologically identified and subjected to a phylogenetic analysis to confirm their identities. Results Seventeen of the 50 Qinghai voles had E. multilocularis-infection-like vesicles in their livers. Eleven out of the 17 Qinghai voles presented E. multilocularis infection, which was detected by PCR and sequencing. The phylogenetic analysis showed that all 11 positive samples belonged to the E. multilocularis Asian genotype. A morphological identification and phylogenetic analysis of the E. multilocularis-infected Qinghai voles confirmed that all captured animals were L. fuscus. Conclusions L. fuscus can be infected with E. multilocularis and plays a potential role in the life cycle and epidemiology of E. multilocularis in the Qinghai-Tibetan Plateau of China.